2022
DOI: 10.1002/agr.21760
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the price effects of honey quality attributes in a European country: Evidence from a hedonic price approach

Abstract: This study investigates the price effects of honey quality attributes in Spain. Price and product characteristics are collected from 264 honey labels found on the shelves of the main representative retail stores available in the national territory. The marginal effects and the implicit prices of honey characteristics are assessed through a hedonic price approach. Results show that the prices of honey are affected by leader brands sold in gourmet stores and hypermarkets in glass packages compared to producer br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Quality of honey has been seen not to affect positively the price of honey as it was not significant difference (P>0.05) hence, no influence on price of honey. The findings are similar to the study by Ballco et al (2022) who reported that the quality of honey from non-EU countries have no any significance in determining the market price of honey in Spain. This shows that most of the honey which comes from developing countries has not yet reached the quality in some of the developed countries.…”
Section: Factor Associated With Determination Of Honey Pricesupporting
confidence: 90%
“…Quality of honey has been seen not to affect positively the price of honey as it was not significant difference (P>0.05) hence, no influence on price of honey. The findings are similar to the study by Ballco et al (2022) who reported that the quality of honey from non-EU countries have no any significance in determining the market price of honey in Spain. This shows that most of the honey which comes from developing countries has not yet reached the quality in some of the developed countries.…”
Section: Factor Associated With Determination Of Honey Pricesupporting
confidence: 90%
“…Bimbo et al (2016) apply a hedonic pricing model to the Italian yogurt market to evaluate the extent to which health claims contribute to product prices, finding that price premiums differ depending on the type of claim. While the hedonic pricing model has been applied to food products such as eggs (Karipidis et al, 2015), honey (Ballco et al, 2022) or alternative dairy beverages (Yang & Dharmasena, 2020), few studies exist for the meat market and, none, that considers the meat and MS market. Ribeiro et al (2019) apply a hedonic pricing model to chicken purchase scanner data and find that UK consumers are willing to pay a 135% or £6.36/kg premium for organic.…”
Section: Introductionmentioning
confidence: 99%